The parasite game: Exploiting the abundance of nature in face of competition - Judith Avrahami; Werner Güth; Yaakov Kareev (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2001)
A situation in which the regularity in nature can be utilized while competition is to be avoided is modelled by the Parasite game. In this game regular behaviour could enhance guessing nature but strategic randomization is required to avoid being outguessed. In an experiment, 60 pairs of participants (partner design) played many rounds of the Parasite game. The treatments differed in nature's probabilities and whether or not these probabilities were announced in advance or could only be experienced over time. Before playing, the working memory (WM) of participants was measured. Data analyses test the correspondence of participants behavior to game-theoretic benchmarks and the effect of participants' WM on their behavior.
urn:nbn:de:kobv:11-10049708
Keywords: 330